For adiabatic process
"A=\\frac{m}{M} \\frac{RT_1}{\\gamma-1}(1-(\\frac{V_1}{V_2})^{\\gamma-1})=\\frac{m}{M} \\frac{RT_1}{\\gamma-1}(1-((\\frac{p_2}{p_1})^{\\frac{1}{\\gamma}})^{\\gamma-1})"
"A=\\frac{m}{M} \\frac{RT_1}{\\gamma-1}(1-((\\frac{p_2}{p_1})^{\\frac{\\gamma-1}{\\gamma}}))"
"\\gamma=\\frac{i+2}{i}=\\frac{5+2}{5}=1.4"
So, we have
"A=\\frac{m}{M} \\frac{RT_1}{\\gamma-1}(1-((\\frac{p_2}{p_1})^{\\frac{\\gamma-1}{\\gamma}}))="
"=\\frac{0.008}{0.032} \\frac{8.31\\cdot 273}{1.4-1}(1-((\\frac{10\\cdot 101325}{101325})^{\\frac{1.4-1}{1.4}}))\\approx-1320J"
Comments
Leave a comment